2008
DOI: 10.1007/s00249-008-0338-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative modeling of selective lysosomal targeting for drug design

Abstract: Lysosomes are acidic organelles and are involved in various diseases, the most prominent is malaria. Accumulation of molecules in the cell by diffusion from the external solution into cytosol, lysosome and mitochondrium was calculated with the Fick-Nernst-Planck-equation. The cell model considers the diffusion of neutral and ionic molecules across biomembranes, dissociation to mono-or bivalent ions, adsorption to lipids, and electrical attraction or repulsion. Based on simulation results, high and selective ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
192
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(200 citation statements)
references
References 34 publications
8
192
0
Order By: Relevance
“…In particular, our calculation of AZM accumulation ratios in the subcellular compartments of PMLs are in agreement with the ratios predicted using another subcellular disposition model (23). In addition to the pH-dependent accumulation of AZM in acidic cell compartments, it has also been shown that the drug can bind in its protonated form to negatively charged phospholipids, which further increases its accumulation in tissues (22,38).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In particular, our calculation of AZM accumulation ratios in the subcellular compartments of PMLs are in agreement with the ratios predicted using another subcellular disposition model (23). In addition to the pH-dependent accumulation of AZM in acidic cell compartments, it has also been shown that the drug can bind in its protonated form to negatively charged phospholipids, which further increases its accumulation in tissues (22,38).…”
Section: Discussionsupporting
confidence: 88%
“…Equation 6 can also be used to compute the differences in f unionized in different cell compartments, e.g., between the cytosol of PMLs (pH ϳ7 [23,24]) and the lysosomes located within PMLs (pH ϳ5 [23,25]). Given that f unionized in the lysosomes is very low (0.000013), we assumed that once AZM is protonated in the acidic environment of lysosomes, it is trapped and thus no longer available for direct exchange with the plasma compartment.…”
Section: Methodsmentioning
confidence: 99%
“…LC-MS/MS analysis was conducted on a Sciex Triple Quad 4000 mass spectrometer (turbospray ionization source) with a (Trapp and Horobin, 2005;Trapp et al, 2008). Key components of the model are illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recent modeling studies by Trapp and coauthors have approached the flux of neutral and ionic compounds into plants and animal cells and organelles by using a dynamic cell model based on the "Fick-Nernst-Planck" equation (a combination of Fick's first law and the Nernst-Planck equation describing the electrochemical potential) (162,(365)(366)(367). Adapting and enhancing this model, Zarfl and colleagues simulated accumulation in cells of a group of antibacterial sulfonamides based on various assumptions about the permeating capability of the anionic species of the compounds (402).…”
Section: Formulation Of Rules For Intracellular Accumulationmentioning
confidence: 99%